The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1074/jbc.m116.762807
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Claudin-2 Expression and Proliferation by Epigenetic Inhibitors in Human Lung Adenocarcinoma A549 Cells

Abstract: Claudin-2 is highly expressed in lung adenocarcinoma tissues and increases proliferation in adenocarcinoma cells. The chemicals that reduce claudin-2 expression may have anti-cancer effects, but such therapeutic medicines have not been developed. We found that azacitidine (AZA), a DNA methylation inhibitor, and trichostatin A (TSA) and sodium butyrate (NaB), histone deacetylase (HDAC) inhibitors, decrease claudin-2 levels. The effect of AZA was mediated by the inhibition of phosphorylated Akt and NF-κB. LY-294… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…The expression of CLDN2 is upregulated by several intracellular signaling pathways, including the PI3K/Akt pathway in A549 cells [10,20]. LY-294002, an inhibitor of PI3K, decreases mRNA levels and promoter activity of CLDN2 [19]. Kaempferide decreased the p-Akt level without affecting the total amount of Akt ( Figure 6).…”
Section: Discussionmentioning
confidence: 97%
“…The expression of CLDN2 is upregulated by several intracellular signaling pathways, including the PI3K/Akt pathway in A549 cells [10,20]. LY-294002, an inhibitor of PI3K, decreases mRNA levels and promoter activity of CLDN2 [19]. Kaempferide decreased the p-Akt level without affecting the total amount of Akt ( Figure 6).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, genetic alteration in claudin-2 expression was sufficient to modulate cyclin-D1 and P-21 expressions in colon cancer cells and modulate growth properties. Similarly, knockdown of claudin-2 by siRNA in lung cancer cells A549 was recently reported to decrease proliferation concomitant with decreases in cyclin-D1 and E1 expression, cell cycle progression factors [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have further reported causal role of the HDACi in regulating EGFR expression (mRNA transcription) and associated signaling using colon cancer cells [ 41 ]. Among claudin proteins, claudin-2 is the most regulated family member as its expression is regulated by the EGFR, C-Met, Ras and PI-3 Kinase signaling [ 3 , 64 , 68 ]. We were the first to demonstrate the key role of EGFR-activation in regulating colonic claudin-2 expression as claudin-2 expression was specifically downregulated in Waved-2 mice, which are defective in EGFR-tyrosine kinase signaling [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional start site of human IRF-3 promoter was set as +1. The truncated human IRF-3 promoter plasmids pGL3-982, pGL3-149, and pGL3-67 were constructed as before [ 9 ]. The software Matlnspector ( http://www.genomatix.de//matinspector.html ) were used to search for IRF-3 promoter sequence for potential transcription factors target sites which are subject to acetylation.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular mechanism of HDACi in lung cancer cells was currently under investigation. Hichino et al demonstrated that A549 cells proliferation was decreased by TSA, which was partially rescued by ectopic expression of claudin-2 [ 9 ]. Entinostat, as a kind of HDACi drugs, has been investigated in SALL4 positive lung caners [ 10 ].…”
Section: Introductionmentioning
confidence: 99%